Biomimetic twisted plywood structural materials. Issue 5 (30th July 2018) - Chen, Si-Ming; Gao, Huai-Ling; Zhu, Yin-Bo; Yao, Hong-Bin; Mao, Li-Bo; Song, Qi-Yun; Xia, Jun; Pan, Zhao; He, Zhen; Wu, Heng-An; Yu, Shu-Hong
Abstract: Biomimetic designs based on micro/nanoscale manipulation and scalable fabrication are expected to develop new-style strong, tough structural materials. Although the mimicking of nacre-like 'brick-and-mortar' structure is well studied, many highly ordered natural architectures comprising 1D micro/nanoscale building blocks still elude imitation owing to the scarcity of efficient manipulation techniques for micro/nanostructural control in practical bulk counterparts. Herein, inspired by natural twisted plywood structures with fascinating damage tolerance, biomimetic bulk materials that closely resemble natural hierarchical structures and toughening mechanisms are successfully fabricated through a programmed and scalable bottom-up assembly strategy. By accurately engineering the arrangement of 1D mineral micro/nanofibers in biopolymer matrix on the multiscale, the resultant composites display optimal mechanical performance, superior to many natural, biomimetic and engineering materials. The design strategy allows for precise micro/nanostructural control at the macroscopic 3D level and can be easily extended to other materials systems, opening up an avenue for many more micro/nanofiber-based biomimetic designs.